Peran Fiksi Realistik Pada Novel Laskar Pelangi Dalam Mempertahankan Nilai BudayaPeran Fiksi Realistik Pada Novel Laskar Pelangi Dalam Mempertahankan Nilai Budaya - Cindy Berliana Latansyah; Dewi Sinta Febriani; Syarifah Aini; Takhta Adi Waskita; Yunita Widyastuti; Eni Nurhayati (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In the era of globalization and information technology, literature plays a crucial role in shaping cultural identity and enriching human knowledge and empathy. This journal discusses the role of realistic fiction in the novel